EDUCATION AND PRACTICAL TRAINING ON THE USE OF SIMPLE BALANCES FOR ELEMENTARY SCHOOL STUDENTS IN BAWONIFAOSO VILLAGE - Darmawan Harefa (Universitas Nias Raya, 2026)
This community service program entitled “Education and Practical Training on the Use of Simple Balances for Elementary School Students in Bawonifaoso Village” aimed to improve students’ understanding of basic science concepts, particularly mass measurement, through hands-on learning activities. The program addressed the common issue in rural elementary schools where science learning is often dominated by theoretical instruction with limited practical experience. To overcome this challenge, the activity was designed using an experiential learning approach involving simple balance tools that are easy to construct, affordable, and suitable for classroom use. The implementation consisted of three main stages: conceptual introduction, practical training, and evaluation. In the conceptual stage, students were introduced to the basic concept of mass and the function of balance instruments. In the practical stage, students worked in groups to measure and compare the mass of various objects using simple balances. The evaluation stage involved observation and simple assessments to measure students’ understanding and skills. The results of the program showed a significant improvement in students’ conceptual understanding, science process skills, and learning motivation. Students became more active, engaged, and confident in conducting simple scientific experiments. In addition, teachers gained new insights into the use of practical learning media that can be applied in daily instruction. Overall, the program demonstrated that the use of simple balances is an effective and sustainable strategy to enhance science learning in elementary schools, particularly in rural areas with limited resources.